Bioinspired engineered nickel nanoparticles with multifunctional attributes for reproductive toxicity - Iftikhar, Mehwish; Noureen, Aasma; Jabeen, Farhat; Uzair, Muhammad; Rehman, Nagina; Sher, Emina Karahmet; Katubi, Khadijah Mohammedsaleh; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Sher, Farooq (Elsevier, 2023)
Nickel nanoparticles (Ni-NPs) have potential applications in high-tech sectors such as battery manufacturing, catalysis, nanotube printing and textile. Apart from their increasing utilisation in daily life, there are concerns about their hazardous nature as they are highly penetrable in biological systems. The carcinogenic and mutagenic ability of Ni-NPs is evident but the research gaps are still there concerning the safety evaluation of Ni-NPs regarding male reproductive ability. This controlled randomized research was planned to assess the male reproductive toxicity of Ni-NPs in Sprague Dawley rats. Ni-NPs of spherical shape and mean particle size of 56 nm were used in the study, characterized by SEM, EDS and XRD. The twenty-five healthy rats (200–220 g) were used for toxicity investigation of Ni-NPs and divided into five groups; negative control (0 Ni-NPs), placebo group (0.9% saline) and three Ni-NPs treated groups (@ 15, 30 and 45 mg/kg BW). The results of 14 days of intraperitoneal exposure to Ni-NPs revealed that a higher dose (45 mg/kg BW) of Ni-NPs caused a significant reduction in body weight, serum testosterone, daily sperm production while the testis index and Ni accumulation and histological changes (necrosis in basement membrane and seminiferous tubules, vacuole formation) in testicular tissues increased with increasing dose of Ni-NPs. It can be concluded from the study that Ni-NPs have potential reproductive toxicity. This study provided the baseline data of Ni-NPs toxicity for the male reproductive system and can be applied for risk assessment in Ni-NPs based products.
Keywords: Histological alterations and lipid peroxidation; Nanoparticles; Oxidative stress; Reproductive toxicity; Serum testosterone; Sperm production